2015
DOI: 10.1159/000440952
|View full text |Cite
|
Sign up to set email alerts
|

Demineralized Dentin Matrix Induces Odontoblastic Differentiation of Dental Pulp Stem Cells

Abstract: The aim of this study was to investigate the effect of demineralized dentin matrix (DDM) on dental pulp stem cells (DPSCs) and the potential of complexes with DPSCs and DDM for mineralized tissue formation. Stem cells derived from the dental pulp of healthy pigs aged 18 months were isolated and cultured. DPSCs were incubated with alpha-minimum essential medium treated with DDM extract at 1 mg/ml (DDM1) or 10 mg/ml (DDM10). The concentrations of 3 growth factors in DDM extract was measured by enzyme-linked immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 46 publications
4
26
0
Order By: Relevance
“…This finding was in concert with that of a previously conducted study, which demonstrated that a new direct pulp‐capping material containing an antibacterial resin monomer as well as Portland cement could potentially enhance the adhesion and migration of DPSCs [Yu et al, ]. A demineralized dentin matrix has displayed its ability in enhancing DPSC adhesion and migration [Liu et al, ]. SOX2 has been shown to promote the proliferation, migration and adhesion of DPSCs, evidence of this was elucidated using similar parameters and mechanisms demonstrated in our study [Liu et al, ].…”
Section: Discussionsupporting
confidence: 90%
“…This finding was in concert with that of a previously conducted study, which demonstrated that a new direct pulp‐capping material containing an antibacterial resin monomer as well as Portland cement could potentially enhance the adhesion and migration of DPSCs [Yu et al, ]. A demineralized dentin matrix has displayed its ability in enhancing DPSC adhesion and migration [Liu et al, ]. SOX2 has been shown to promote the proliferation, migration and adhesion of DPSCs, evidence of this was elucidated using similar parameters and mechanisms demonstrated in our study [Liu et al, ].…”
Section: Discussionsupporting
confidence: 90%
“…However, at low concentrations of 0.1 µg/mL, DDM presented a chemo-attractant role, inducing migration of cells through a collagen matrix, whilst 10 µg/mL inhibited cell migration. Similar actions for DDM preparations have been noted for dental pulp stem cells (Lee et al, 2015;Gonçalves et al, 2016;Liu et al, 2016) although it should be noted that for these studies the demineralised dentine extract was prepared using different protocols that varied around the theme of demineralising the mineralised tissue and thus would lead to DDM of different composition to that identified in the present study. As a direct comparison, for DDM prepared following the same protocol (Lee et al, 2015), the up-regulation of bone forming markers in dental pulp stem cells has been shown to be induced with DDM at 1 µg/ mL, with 10 µg/mL DDM significantly increasing cell proliferation, thus highlighting differential effects of DDM on cells from different tissue sources.…”
Section: Discussionsupporting
confidence: 63%
“…Placement of dentine in vivo has been reported to stimulate reparative bone formation in rabbit critical defects (Gomes et al, 2008) and in rat tooth sockets (de Oliveira et al, 2013). In vitro, DDM has been demonstrated to induce mineralisation and increased expression of bone forming markers of human DPSCs (Lee et al, 2015;Gonçalves et al, 2016;Liu et al, 2016) and murine bone marrow MSCs (BMMSCs) (Yu et al, 2014). Proteomic studies of human dentine have identified the presence of up to 289 different components, with TGF-β1 identified as a prominent growth factor (Jágr et al, 2012;Chun et al, 2011;Park et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…ALP plays a special role in the mineralization of bone and dentin matrix, by exhibiting gradual increase at the beginning of odontoblastic differentiation. 32 In our study, GSE did not interfere in the secretion of ALP in either cell line investigated, and could be evidenced by staining in culture wells. In addition, the extract increased ALP deposition significantly in both cell lines.…”
Section: Discussionsupporting
confidence: 55%